Secondary battery and electric device

CN119318046APending Publication Date: 2025-01-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380044912.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

During the charging and discharging process of existing secondary batteries, the volume expansion rate of silicon-based materials is large, resulting in poor cycle performance, and repeated regeneration of the solid electrolyte interface film on the surface increases the internal resistance of the battery and reduces the capacity retention rate.

Method used

A silicon-carbon composite material with a three-dimensional network cross-linked pore structure is used as the negative electrode material, and a cyclic carbonate compound is added to the electrolyte to form a stable interface film, reduce the internal resistance of the battery, and improve cycle performance.

Benefits of technology

Through the combination of the porous skeleton of the silicon-carbon composite material and the cyclic carbonate compound, the volume change of silicon during charge and discharge is effectively reduced, the cycle capacity retention rate and energy density of the battery are improved, the gas production is reduced, and the cycle stability and stability of the battery are improved. Dynamic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318046A_ABST
    Figure CN119318046A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery. The secondary battery comprises a negative pole piece and an electrolyte, wherein the negative pole piece comprises a silicon-carbon composite material with a three-dimensional network cross-linked pore structure; the electrolyte contains a cyclic carbonate compound represented by formula I. Through the cooperation of the three-dimensional network cross-linked pore structure of the silicon-carbon composite material and the cyclic carbonate compound in the electrolyte, the volume effect of the active material in the charge-discharge process is inhibited, the direct-current impedance and the gas production rate of the battery are reduced, and the cycle capacity retention rate of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Secondary batteries and electrical devices Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.

[0003] Electrode active materials with high gram capacity often have poor cycle performance. How to improve the battery energy density while taking into account excellent cycle performance through the mutual coordination of various battery components is a technical problem that needs to be solved urgently in this field.

[0004] Summary of the Invention

[0005] This application is made in view of the above-mentioned problems, and its purpose is to provide a secondary battery. By matching the electrolyte and the negative electrode material, the volume effect of the active material during the charge and discharge process is suppressed, the DC impedance of the battery is reduced, and the cycle capacity retention rate of the battery is improved.

[0006] The first aspect of the present application provides a secondary battery comprising: a negative electrode plate and an electrolyte; the negative electrode plate comprises a silicon-carbon composite material having a three-dimensional network cross-linked pore structure, and the electrolyte comprises a cyclic carbonate compound.

[0007] The cyclic carbonate compound is represented by formula I,

[0008] Wherein, R1 and R2 each independently include at least one of H and C1-C6 alkyl.

[0009] Silicon-carbon composites with a three-dimensional network cross-linked pore structure possess a stable porous framework and good mechanical strength. They can effectively reduce the volume change of silicon before and after charge and discharge while loading a high silicon content. Furthermore, the cyclic carbonate compound used in the electrolyte can be used to construct an interfacial component on the surface of the silicon-carbon composite, forming a stable interfacial film, reducing the battery's internal resistance and improving cycle performance.

[0010] In any embodiment, the pore volume per unit mass of the silicon-carbon composite material is Vm, in cm 3 / g; in the electrolyte, based on the total mass of the electrolyte, the mass proportion of the cyclic carbonate compound is EL, the unit is g / g, EL:Vm is 0.02 to 5, and can be optionally 0.05 to 3.5.

[0011] When the ratio EL:Vm between the pore volume Vm of the silicon-carbon composite material and the mass proportion EL of the cyclic carbonate compound in the electrolyte meets the above range, the amount of cyclic carbonate compound added can be coordinated with the pore volume Vm of the silicon-carbon composite material, thereby improving the cycle capacity retention rate of the battery. At the same time, the addition of cyclic carbonate with an appropriate mass content can also reduce the decomposition gas production caused by excessive addition of cyclic carbonate or the preferential decomposition gas production of other solvents caused by insufficient addition of cyclic carbonate, thereby reducing the volume expansion caused by gas production and further improving the cycle performance.

[0012] In any embodiment, the pore volume per unit mass of the silicon-carbon composite material is Vm in the range of 0.01 to 0.3 cm 3 / g, optional range is 0.02~0.15cm 3 / g.

[0013] When the pore volume of the silicon-carbon composite material meets the above range, it can not only ensure its mechanical strength, but also ensure the silicon loading capacity. It can also improve the battery cycle performance through effective cooperation with the cyclic carbonate compound in the electrolyte, and can avoid the gas production caused by excessive addition of cyclic carbonate.

[0014] In any embodiment, in the electrolyte, based on the total mass of the electrolyte, the mass ratio of the cyclic carbonate compound is EL, and the unit is g / g. The specific surface area of ​​the silicon-carbon composite material is SSA, and EL:SSA is 0.00001 to 0.15, and can be optionally 0.00015 to 0.05.

[0015] When the ratio EL:SSA between the mass proportion of the cyclic carbonate compound in the electrolyte and the specific surface area SSA of the silicon-carbon composite material meets the above range, the cyclic carbonate compound can be effectively embedded in the pore structure of the silicon-carbon composite material, fully contact with the silicon-carbon composite material, form a uniform interface film, improve the interface stability, thereby reducing the internal resistance of the battery and improving the cycle stability of the battery; at the same time, it can also reduce the decomposition and gas production caused by excessive addition of cyclic carbonate or the preferential decomposition and gas production of other solvents caused by insufficient addition of cyclic carbonate, reduce the volume expansion caused by gas production, and further improve the cycle performance.

[0016] In any embodiment, the specific surface area SSA of the silicon-carbon composite material is 2 to 10 m 2 / g; 3~7m can be selected 2 / g.

[0017] When the specific surface area SSA of the silicon-carbon composite material meets the above range, the specific surface area of ​​the silicon-carbon composite material is large and the dynamic properties of the material are good.

[0018] In any embodiment, the total pore volume of the pores with a pore diameter of less than or equal to 100 nm in the silicon-carbon composite material is V1cm 3 / g, in the electrolyte, based on the total mass of the electrolyte, the mass proportion of the cyclic carbonate compound is EL, the unit is g / g, EL:V1 is 0.05 to 50, and can be optionally 1 to 30.

[0019] When the ratio EL:V1 between the mass proportion EL of the cyclic carbonate compound in the electrolyte and the total pore volume V1 of pores with a pore diameter less than or equal to 100 nm in the silicon-carbon composite material is within the above range, the cyclic carbonate compound can easily enter the pore structure of the silicon-carbon composite material, forming mutual cooperation with it to further increase the migration rate of ions in the electrode active material and improve the cycle performance of the battery.

[0020] In any embodiment, the silicon-carbon composite material has a V1 of ≥ 0.001 cm 3 / g, optional range is 0.005~0.01cm 3 / g.

[0021] When V1 of the silicon-carbon composite material is within the above range, the silicon-carbon composite material can effectively cooperate with the cyclic carbonate compound in the electrolyte to improve the cycle performance of the battery; and can avoid gas production caused by excessive addition of cyclic carbonate.

[0022] In any embodiment, the cyclic carbonate compound is selected from at least one of ethylene carbonate, propylene carbonate, 1,2-butanediol carbonate, and 4,5-dimethylethylene carbonate.

[0023] The cyclic carbonate compound has a high dielectric constant and high ionic conductivity, and can be used to construct interface components, form a stable interface film, and improve the cycle performance of the battery.

[0024] In any embodiment, the silicon-carbon composite material includes: a carbon matrix and silicon nanoparticles, the carbon matrix has a three-dimensional network cross-linked pore structure; the silicon nanoparticles are at least partially embedded in the three-dimensional network cross-linked pore structure of the carbon matrix.

[0025] When the silicon-carbon composite material having the above structure is applied to a secondary battery, it can achieve a simultaneous improvement in the cycle performance and energy density of the secondary battery.

[0026] In any embodiment, the mass ratio of the silicon nanoparticles in the silicon-carbon composite material is greater than or equal to 40%, and can be optionally 40-60%.

[0027] The negative electrode material used in the secondary battery of the present application achieves a high loading amount of silicon nanoparticles in the negative electrode material by adopting a carbon-based material having a three-dimensional network cross-linked pore structure, so that the silicon-carbon composite material has a high capacity and can further improve the energy density of the battery.

[0028] In any embodiment, the silicon nanoparticles include one or more of silicon oxides, pre-lithium silicon oxides, amorphous silicon, crystalline silicon, and silicon-carbon composites.

[0029] In any embodiment, the carbon matrix includes one or more of graphite, soft carbon, and hard carbon.

[0030] In any embodiment, the total volume of pores with a pore diameter greater than 100 nm in the carbon matrix particles is recorded as Vc1cm 3 / g, the total volume of the pores with a pore diameter of less than or equal to 100 nm in the carbon matrix particles is recorded as Vc2cm 3 / g, the carbon matrix particles satisfy: 1<Vc2 / Vc1≤30; optionally, 3≤Vc2 / Vc1≤25.

[0031] By regulating the total pore volume ratio of pores of a specific size in the porous carbon matrix particles, the pore size distribution of the carbon matrix particles can be made moderate, which can ensure that the silicon-carbon composite material has a high silicon loading and mechanical strength. It can also form an effective coordination with the molecular structure of the electrolyte through the large and small pore sizes, thereby improving the ion transfer rate in the electrolyte and optimizing the kinetic performance.

[0032] In any embodiment, the powder compaction density of the silicon-carbon composite material after one powder compaction test under a force of 20,000 N is P11 g / cm 3 The compaction density of the silicon-carbon composite material after 20 times of powder compaction under a force of 20000N is P21g / cm 3 The ratio satisfies: 1.00<P21 / P11≤1.20, optionally, 1.02≤P21 / P11≤1.10.

[0033] When the ratio of P21 / P11 satisfies the above range, the silicon-carbon composite material has a higher gram capacity and better compressive resistance, thereby improving the structural stability of the negative electrode film layer, so that the secondary battery containing this material has a higher energy density while also having better cycle performance.

[0034] In any embodiment, the powder compaction density of the silicon-carbon composite material after one powder compaction test under a force of 20,000 N is P11 g / cm 3 Satisfies: 1.10≤P11≤1.40, optionally, 1.12≤P11≤1.35.

[0035] The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 When the above range is met, the negative electrode film layer has a higher compaction density, so that the secondary battery has a higher energy density.

[0036] In any embodiment, the secondary battery includes at least one of a lithium ion battery, a sodium ion battery, a magnesium ion battery, and a potassium ion battery.

[0037] A second aspect of the present application provides an electrical device comprising the secondary battery of the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0039] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;

[0040] FIG3 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0041] Description of reference numerals: 1 secondary battery; 11 housing; 12 electrode assembly; 13 cover plate. DETAILED DESCRIPTION

[0042] Below, the embodiments of the binder, preparation method, electrode, battery, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0043] " scope " disclosed in the application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and selected lower limit and upper limit define the boundary of special scope. The scope that this mode limits can be to include end value or not include end value, and can be combined arbitrarily, and promptly any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 listed, and if the maximum range value 3,4 and 5 are listed, then the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0044] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0045] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0046] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0047] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0048] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0049] As the application scope of secondary batteries expands, the requirements for secondary battery performance, such as energy density, are gradually increasing. Silicon-based materials have high specific capacity and are suitable negative electrode materials for high-energy-density batteries. However, silicon-based materials have a large volume expansion rate during the charge and discharge process, resulting in poor battery cycle performance. In addition, the solid electrolyte interface film (SEI film) on its surface will repeatedly regenerate as the silicon-based material expands, increasing the internal resistance of the battery and reducing the capacity retention rate.

[0050] Based on this, the present application proposes a secondary battery, which includes: a negative electrode plate and an electrolyte, wherein the negative electrode plate includes a silicon-carbon composite material having a three-dimensional network cross-linked pore structure; the electrolyte contains a cyclic carbonate compound, and the cyclic carbonate compound is represented by Formula I,

[0051] Wherein, R1 and R2 are each independently selected from H and C1-C6 alkyl.

[0052] In this article, the three-dimensional network cross-linked pore structure generally refers to a structure in which two or more pores are interconnected or interlaced and share pore volume in a silicon-carbon composite material, especially in a pore structure formed by carbon matrix particles.

[0053] The pore structure of the silicon-carbon composite material can be tested using equipment and methods known in the art. For example, it can be tested by using a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be followed: first, the negative electrode sheet containing the silicon-carbon composite material is cut into a sample to be tested of a certain size (for example, 6 mm × 6 mm), and the sample to be tested is clamped with two conductive and heat-conductive thin sheets (such as copper foil), and the sample to be tested and the thin sheet are glued and fixed with glue (such as double-sided tape), and a flat iron block of a certain mass (such as about 400 g) is used to press for a certain time (such as 1 hour) to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors and glued to a sample table with conductive glue, and the sample is slightly protruding from the edge of the sample table. Then, place the sample stage into the sample holder and lock it securely. Turn on the power of the argon ion cross-section polisher (e.g., IB-19500CP) and evacuate the sample to a vacuum (e.g., 10 Pa to 4 Pa). Set the argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours). Adjust the sample stage to the rocking mode and start polishing. After polishing, use a scanning electron microscope (e.g., ZEISS Sigma 300) to obtain an ion polished cross-section morphology (CP) image of the sample to be tested.

[0054] Silicon-carbon composites with a three-dimensional network cross-linked pore structure possess a stable porous framework and good mechanical strength. They can effectively reduce the volume change of silicon before and after charge and discharge while loading a high silicon content. Furthermore, the cyclic carbonate compound used in the electrolyte can be used to construct an interfacial component on the surface of the silicon-carbon composite, forming a stable interfacial film, reducing the battery's internal resistance and improving cycle performance.

[0055] In some embodiments, the pore volume per unit mass of the silicon-carbon composite material is Vm, cm 3 / g, in the electrolyte, based on the total mass of the electrolyte, the mass proportion of the cyclic carbonate compound is EL, and the unit is g / g, and the ratio EL:Vm between the pore volume Vm of the silicon-carbon composite material and the mass proportion EL of the cyclic carbonate compound in the electrolyte is 0.02 to 5, and can be optionally 0.05 to 3.5.

[0056] In some embodiments, the ratio EL:Vm between the pore volume Vm of the silicon-carbon composite material and the mass proportion EL of the cyclic carbonate compound in the electrolyte can be selected as 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5.

[0057] The pore volume Vm of silicon-carbon composite materials can be calculated using the following formula: Among them, ρ 真 Represents the true density of the silicon-carbon composite material, and α represents the porosity of the silicon-carbon composite material. Porosity refers to the ratio of the pore volume within the particle to the total volume of the carbon matrix particle. Porosity can be measured by the gas replacement method in accordance with GB / T24586. Porosity W = (L1-L2) / L1*100%, where L1 is the apparent volume of the sample and L2 is the true volume of the sample. True density is a well-known meaning in the art, which refers to the actual mass of a solid substance per unit volume when the material is absolutely dense, that is, the density after removing the voids inside the material or the voids between particles; it can be tested using instruments and methods known in the art. For example, the test method can refer to GB / T 24586-2009, and the test instrument can be a true density tester. As an example, the following steps can be followed: place a clean and dry sample cup on a balance, reset the balance to zero, add a certain amount of powder sample into the sample cup (for example, the sample can occupy 1 / 2 of the volume of the sample cup), record the mass of the sample, place the sample cup containing the sample in a true density tester for a closed test, introduce helium, detect the pressure of the gas in the sample chamber and the expansion chamber, and then calculate the true volume and, in turn, the true density according to Bohr's law.

[0058] When the ratio EL:Vm between the pore volume Vm of the silicon-carbon composite material and the mass proportion EL of the cyclic carbonate compound in the electrolyte meets the above range, the amount of cyclic carbonate compound added can be coordinated with the pore volume Vm of the silicon-carbon composite material, thereby improving the cycle capacity retention rate of the battery. At the same time, the addition of cyclic carbonate with an appropriate mass content can also reduce the decomposition gas production caused by excessive addition of cyclic carbonate or the preferential decomposition gas production of other solvents caused by insufficient addition of cyclic carbonate, thereby reducing the volume expansion caused by gas production and further improving the cycle performance.

[0059] In some embodiments, the pore volume per unit mass of the silicon-carbon composite material is Vm in the range of 0.01 to 0.3 cm 3 / g, optional range is 0.02~0.15cm 3 / g.

[0060] In some embodiments, the pore volume per unit mass of the silicon-carbon composite material is Vm, which can be selected from 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29 or 0.3.

[0061] When the pore volume of the silicon-carbon composite material meets the above range, it can not only ensure its mechanical strength, but also ensure the silicon loading capacity. It can also improve the battery cycle performance through effective cooperation with the cyclic carbonate compound in the electrolyte, and can avoid the gas production caused by excessive addition of cyclic carbonate.

[0062] In some embodiments, in the electrolyte, based on the total mass of the electrolyte, the mass ratio of the cyclic carbonate compound is EL, and the unit is g / g. The specific surface area of ​​the silicon-carbon composite material is SSA, and EL:SSA is 0.00001 to 0.15, and can be optionally 0.00015 to 0.05.

[0063] In some embodiments, the ratio EL:SSA between the mass proportion of the cyclic carbonate compound in the electrolyte and the specific surface area SSA of the silicon-carbon composite material may be 0.00015, 0.00016, 0.00017, 0.00018, 0.00019, 0.0002, 0.0003, 0.0004, 0.0005, 0.0006, 0.0007, 0.0008, 0.0009, 0.001, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04 or 0.05.

[0064] In this article, specific surface area SSA is a well-known meaning in the art, usually the surface area is expressed in m 2 The unit of % is expressed in g and can be measured using methods and instruments known in the art. For example, it can be measured using an inert gas (e.g., nitrogen) adsorption specific surface area analysis method according to GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis can be performed using a Tri-Star 3020 specific surface area pore size analyzer from Micromeritics, USA.

[0065] When the ratio EL:SSA between the mass proportion of the cyclic carbonate compound in the electrolyte and the specific surface area SSA of the silicon-carbon composite material meets the above range, the cyclic carbonate compound can be effectively embedded in the pore structure of the silicon-carbon composite material, fully contact with the silicon-carbon composite material, form a uniform interface film, improve the interface stability, thereby reducing the internal resistance of the battery and improving the cycle stability of the battery; at the same time, the addition of cyclic carbonate with an appropriate mass content can also reduce the decomposition and gas production of cyclic carbonate due to excessive addition or the preferential decomposition and gas production of other solvents due to insufficient addition of cyclic carbonate, reduce the volume expansion caused by gas production, and further improve the cycle performance.

[0066] In some embodiments, the specific surface area SSA of the silicon-carbon composite material is 2 to 10 m 2 / g; 3~7m can be selected 2 / g

[0067] In some embodiments, the specific surface area SSA of the silicon-carbon composite material can be selected to be 2 m 2 / g、3m 2 / g、4m 2 / g、5m 2 / g、6m 2 / g、7m 2 / g、8m 2 / g、9m 2 / g or 10m 2 / g, or a range consisting of any two of the above values.

[0068] When the specific surface area SSA of the silicon-carbon composite material meets the above range, the specific surface area of ​​the silicon-carbon composite material is large and the dynamic properties of the material are good.

[0069] In some embodiments, the total pore volume of pores with a pore diameter of less than or equal to 100 nm in the silicon-carbon composite material is V1 cm 3 / g, in the electrolyte, based on the total mass of the electrolyte, the mass proportion of the cyclic carbonate compound is EL, the unit is g / g, EL:V1 is 0.05 to 50, and can be optionally 1 to 30.

[0070] The pore volume test method for different pore sizes can refer to GB / T 19587-2004, using the mesopore pore size distribution test BJH (Barret Joyner Halenda), using the gas adsorption and desorption method under the micro-mesopore model and selecting the adsorption branch data to measure and calculate the total pore volume V1 of pores with a pore size of less than or equal to 100 nm.

[0071] In some embodiments, the ratio EL:V1 between the mass proportion EL of the cyclic carbonate compound in the electrolyte and the total pore volume V1 of pores with a pore diameter less than or equal to 100 nm in the silicon-carbon composite material can be selected as 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45 or 50.

[0072] When the ratio EL:V1 between the mass proportion EL of the cyclic carbonate compound in the electrolyte and the total pore volume V1 of pores with a pore diameter less than or equal to 100 nm in the silicon-carbon composite material is within the above range, the cyclic carbonate compound can easily enter the pore structure of the silicon-carbon composite material, forming mutual cooperation with it to further increase the migration rate of ions in the electrode active material and improve the cycle performance of the battery.

[0073] In some embodiments, the silicon-carbon composite material has a V1 ≥ 0.001 cm 3 / g, optional range is 0.005~0.01cm 3 / g.

[0074] In some embodiments, the V1 of the silicon-carbon composite material may be 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009 or 0.01 cm 3 / g.

[0075] When V1 of the silicon-carbon composite material is within the above range, the silicon-carbon composite material can effectively cooperate with the cyclic carbonate compound in the electrolyte to improve the cycle performance of the battery; and can avoid gas production caused by excessive addition of cyclic carbonate.

[0076] In some embodiments, the cyclic carbonate compound is selected from at least one of ethylene carbonate, propylene carbonate, 1,2-butanediol carbonate, and 4,5-dimethylethylene carbonate.

[0077] The cyclic carbonate compound has a high dielectric constant and high ionic conductivity, and can be used to construct interface components, form a stable interface film, and improve the cycle performance of the battery.

[0078] In some embodiments, the silicon-carbon composite material includes: a carbon matrix and silicon nanoparticles, the carbon matrix has a three-dimensional network cross-linked pore structure, and the silicon nanoparticles are at least partially embedded in the three-dimensional network cross-linked pore structure of the carbon matrix.

[0079] The carbon matrix particles of the present application have a stable porous skeleton structure, a strong supporting capacity, a high stress capacity, and excellent mechanical properties and electrical conductivity; the carbon matrix particles include a three-dimensional network cross-linked pore structure, which provides more space for embedding silicon-based nanoparticles, can be used for large-scale silicon storage, and effectively increase the loading capacity of silicon in the silicon-carbon composite material. After the carbon matrix particles are compounded with the silicon-based nanoparticles, the electrical conductivity of the silicon-carbon composite material can be improved, while the volume effect of silicon in the process of lithium insertion and extraction can be alleviated, and the stress changes of the silicon-based nanoparticles can be fully withstood, thereby ensuring the structural stability of the silicon-carbon composite material and further improving the cycle performance of the battery. Therefore, when the silicon-carbon composite material provided in the present application is applied to a secondary battery, it is possible to achieve a simultaneous improvement in the cycle performance and energy density of the secondary battery.

[0080] In some embodiments, the mass ratio of silicon nanoparticles in the silicon-carbon composite material is greater than or equal to 40%, and can be optionally 40-60%.

[0081] In some embodiments, the mass ratio of silicon nanoparticles in the silicon-carbon composite material may be 40%, 45%, 50%, 55% or 60%.

[0082] The quality of silicon nanoparticles in silicon-carbon composite materials can be tested using methods and equipment known in the art, for example, it can be measured with reference to EPA 6010D-2014 standard; specifically, ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) testing can be used, in which the solid to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then restored to the ground state from the excited state; in the above process, energy is released and recorded as different characteristic spectral lines for quantitative analysis of trace elements.

[0083] The negative electrode material used in the secondary battery of the present application achieves a high loading amount of silicon nanoparticles in the negative electrode material by adopting a carbon-based material having a three-dimensional network cross-linked pore structure, so that the silicon-carbon composite material has a high capacity and can further improve the energy density of the battery.

[0084] In some embodiments, the silicon nanoparticles include one or more of silicon oxides, amorphous silicon, crystalline silicon, and silicon-carbon composites.

[0085] In some embodiments, the carbon matrix includes one or more of graphite, soft carbon, and hard carbon.

[0086] In some embodiments, the total volume of pores with a pore diameter greater than 100 nm in the carbon matrix particles is recorded as Vc1cm 3 / g, the total volume of the pores with a pore diameter of less than or equal to 100 nm in the carbon matrix particles is recorded as Vc2cm 3 / g, the carbon matrix particles satisfy: 1<Vc2 / Vc1≤30; optionally, 3≤Vc2 / Vc1≤25.

[0087] By regulating the total pore volume ratio of pores of a specific size in the porous carbon matrix particles, the pore size distribution of the carbon matrix particles can be made moderate, which can ensure that the silicon-carbon composite material has a high silicon loading and mechanical strength. It can also form an effective coordination with the molecular structure of the electrolyte through the large and small pore sizes, thereby improving the ion transfer rate in the electrolyte and optimizing the kinetic performance.

[0088] In some embodiments, the powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 The compaction density of the silicon-carbon composite material after 20 times of powder compaction under a force of 20,000 N is P21 g / cm 3 The ratio satisfies: 1.00<P21 / P11≤1.20, optionally, 1.02≤P21 / P11≤1.10.

[0089] When the ratio of P21 / P11 satisfies the above range, the silicon-carbon composite material has a higher gram capacity and better compressive resistance, thereby improving the structural stability of the negative electrode film layer, so that the secondary battery containing this material has a higher energy density while also having better cycle performance.

[0090] In some embodiments, the powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 Satisfies: 1.10≤P11≤1.40, optionally, 1.12≤P11≤1.35.

[0091] The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 When the above range is met, the negative electrode film layer has a higher compaction density, so that the secondary battery has a higher energy density.

[0092] In some embodiments, a secondary battery includes a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0093] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0094] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0095] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0096] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0097] In some embodiments, the negative electrode film layer may optionally further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0098] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0099] In some embodiments, a secondary battery includes a positive electrode sheet, which includes a positive electrode collector and a positive electrode film layer disposed on at least one surface of the positive electrode collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.

[0100] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.

[0101] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0102] In some embodiments, the positive electrode active material may adopt the positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0103] In some embodiments, the positive electrode active material is a nickel-rich material, and the molar ratio of nickel in the transition metal of the positive electrode active material is higher than 85%.

[0104] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.

[0105] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0106] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0107] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0108] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0109] In some embodiments, the secondary battery includes at least one of a lithium ion battery, a sodium ion battery, a magnesium ion battery, and a potassium ion battery.

[0110] In one embodiment of the present application, an electric device is provided, comprising the secondary battery of any embodiment.

[0111] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 1 with a square structure as an example.

[0112] In some embodiments, referring to Figure 2, the outer packaging may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the secondary battery 1 can be one or more, and those skilled in the art can select according to specific actual needs.

[0113] An electrical device includes the secondary battery provided in this application. The secondary battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.

[0114] Figure 3 shows an example of an electric device. This device can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0115] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0116] Example

[0117] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0118] Primary and secondary batteries

[0119] Example 1

[0120] (1) Preparation of silicon-carbon composite materials

[0121] A gas containing a silicon precursor is supplied to carbon matrix particles having a three-dimensional network cross-linked pore structure; silicon nanoparticles attached to the carbon matrix particles are generated from the silicon precursor by chemical vapor deposition to obtain a silicon-carbon composite material. The silicon precursor is silane, and the carbon matrix is ​​hard carbon.

[0122] The total volume of pores with a diameter of 100 nm or less in the carbon matrix particles is recorded as Vc2cm 3 / g, the total volume of pores with a pore diameter greater than 100 nm in the carbon matrix particles is recorded as Vc1cm 3 / g, Vc2 / Vc1 is 10.5. The powder compaction density P11 of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is 1.11 g / cm 3 The ratio of the compaction density of the silicon-carbon composite material after 20 times of powder compaction under a force of 20,000 N, P21 to P11, is 1.02.

[0123] (2) Preparation of negative electrode sheet

[0124] The negative electrode active material (silicon-carbon composite material), conductive carbon black, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber latex (SBR) are fully stirred and mixed in an appropriate amount of deionized water at a weight ratio of 96.5:1.0:1.0:1.5 to form a uniform negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying and other processes, a negative electrode sheet is obtained.

[0125] (3) Preparation of positive electrode sheet

[0126] Aluminum foil with a thickness of 8 μm was used as the positive electrode current collector. 0.8 Co 0.1 Mn 0.1 O2(NCM 811 ), the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) are dissolved in the solvent N-methylpyrrolidone (NMP) in a weight ratio of 93:2:5, and the mixture is fully stirred to obtain a positive electrode slurry; the positive electrode slurry is then evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain a positive electrode sheet.

[0127] (4) Preparation of electrolyte

[0128] Fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:3:1 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L, and 5 wt% of ethylene carbonate is added and mixed evenly.

[0129] (5) Isolation membrane

[0130] Polypropylene film is used as the isolation film.

[0131] (6) Preparation of batteries

[0132] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrode sheets to provide isolation. The cells are then wound to obtain a bare cell. The tabs are welded to the bare cell and placed in an aluminum shell. The cells are then baked at 80°C to remove moisture. The electrolyte is then injected and sealed to obtain an uncharged battery. The uncharged battery then undergoes a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the lithium-ion battery product of Example 1.

[0133] Examples 2-4

[0134] The preparation methods of the batteries of Examples 2-4 are similar to those of Example 1, except that the type of cyclic carbonate is adjusted. The specific parameters are shown in Table 1.

[0135] Examples 5-8

[0136] The preparation methods of the batteries of Examples 5-8 are similar to that of Example 1, except that the added content of ethylene carbonate is adjusted. The specific parameters are shown in Table 1.

[0137] Examples 9-12

[0138] The preparation methods of the batteries of Examples 9-12 are similar to those of Example 1, but the mass proportion EL of the cyclic carbonate compound in the electrolyte and the ratio of large and small pores in the three-dimensional network cross-linked pore structure are adjusted. The specific parameters are shown in Table 1.

[0139] Comparative Example 1

[0140] Comparative Example 1 is substantially the same as Example 1, except that the cyclic carbonate compound is not added to the electrolyte.

[0141] Comparative Example 2

[0142] Comparative Example 2 is substantially the same as Example 1, but the pore structure of the carbon matrix particles in Comparative Example 2 is a honeycomb pore structure.

[0143] Comparative Example 3

[0144] Comparative Example 3 is substantially the same as Example 2, but the pore structure of the carbon matrix particles in Comparative Example 3 is a honeycomb pore structure.

[0145] 2. Test Method

[0146] 1. Silicon-carbon composite materials

[0147] 1) Structural characterization of silicon-carbon composites

[0148] The pore structure of the silicon-carbon composite material can be tested using equipment and methods known in the art. For example, it can be tested by using a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be followed: first, the negative electrode sheet containing the silicon-carbon composite material is cut into a sample to be tested of a certain size (for example, 6 mm × 6 mm), and the sample to be tested is clamped with two conductive and heat-conductive thin sheets (such as copper foil), and the sample to be tested and the thin sheet are glued and fixed with glue (such as double-sided tape), and a flat iron block of a certain mass (such as about 400 g) is used to press for a certain time (such as 1 hour) to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors and glued to a sample table with conductive glue, and the sample is slightly protruding from the edge of the sample table. Then, place the sample stage into the sample holder and lock it securely. Turn on the power of the argon ion cross-section polisher (e.g., IB-19500CP) and evacuate the sample to a vacuum (e.g., 10 Pa to 4 Pa). Set the argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours). Adjust the sample stage to the rocking mode and start polishing. After polishing, use a scanning electron microscope (e.g., ZEISS Sigma 300) to obtain an ion polished cross-section morphology (CP) image of the sample to be tested.

[0149] 2) Porosity of silicon-carbon composite materials

[0150] After disassembling the battery, the negative electrode was removed and powder was scraped off. The powder was then ablated at high temperature to remove the binder to obtain a silicon-carbon composite material sample. The sample was measured using the gas displacement method according to GB / T 24586. The porosity (P) is calculated as (V1 - V2) / V1 * 100%, where V1 is the apparent volume of the sample and V2 is the actual volume.

[0151] 3) Specific surface area SSA of silicon-carbon composite material

[0152] The specific surface area was tested using the gas adsorption method according to the GB / T19587-2017 test standard, as follows: a silicon-carbon composite material was taken as a sample, the sample tube was immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures was measured at a relative pressure of 0.05-0.30. The monolayer adsorption amount of the sample was obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of ​​the negative electrode active material.

[0153] The BET calculation formula is as follows:

[0154] Where n a —amount of adsorbed gas, in mol / g; p / p0 —relative pressure; nm —monolayer adsorption capacity; C represents a correction parameter, which is used to limit the number of adsorption layers on the adsorbent surface.

[0155] 4) Pore diameter of silicon-carbon composite material

[0156] The pore size is tested by gas adsorption method according to the test standards GB / T19587-2017 & GB / T21650.2-2008. The specific test method is as follows: a silicon-carbon composite material is taken as a sample, and the sample tube is immersed in liquid nitrogen at -196°C. Nitrogen is adsorbed on the material to be tested at a relative pressure of 0-1. The pore size distribution of the porous material is characterized based on the relationship between the volume of each pore size and the corresponding partial pressure.

[0157] 5) True density of silicon-carbon composite materials

[0158] Referring to GB / T 24586-2009, a true density tester can be used as the testing instrument. For example, the following steps can be followed: Place a clean, dry silicon-carbon composite sample cup on a balance, reset the balance, add a certain amount of powder sample to the cup (for example, the sample can occupy 1 / 2 of the cup's volume), record the mass of the sample, place the sample cup in a true density tester at 25 degrees for a sealed test, introduce helium, test the pressure of the gas in the sample chamber and expansion chamber, and then calculate the true volume and, therefore, the true density, based on Bohr's law.

[0159] 6) Characterization of silicon and carbon element distribution in silicon-carbon composites

[0160] The elemental distribution of the particle cross section was tested by energy dispersive ion polishing cross section element analysis according to the GB-T17359-2012 test standard.

[0161] 2. Battery performance

[0162] 1) Cycle capacity retention rate

[0163] At 25°C, the secondary batteries prepared in each example and comparative example were charged at a constant current rate of 0.5C to a charge cutoff voltage of 4.25V. They were then charged at a constant voltage rate to a current of ≤0.05C, allowed to rest for 5 minutes, and then discharged at a constant current rate of 0.33C to a discharge cutoff voltage of 2V, allowed to rest for 5 minutes. This constituted one charge-discharge cycle. The batteries were subjected to cyclic charge-discharge testing using this method, and the capacity retention of the lithium-ion batteries after 800 cycles was calculated.

[0164] 2) Gas production test

[0165] At room temperature, the secondary batteries prepared in each example and comparative example were charged at a constant current rate of 0.33C to a charge cutoff voltage of 4.25V. They were then charged at a constant voltage to a current of ≤0.05C and allowed to rest for 20 minutes. After storage at 60°C for 90 days, the batteries were removed and tested for gas production. The gas production per unit capacity was calculated by dividing the gas production by the battery capacity.

[0166] 3) Battery internal resistance

[0167] At 25°C, the lithium-ion batteries prepared in each example and comparative example, as well as the lithium-ion battery that had been cycled 800 times at 25°C, were charged at a constant current of 1C to 4.25V. They were then charged at a constant voltage of 4.25V until the current was less than 0.05C, and then discharged at 1C for 30 minutes, adjusting the battery capacity to 50% SOC. The positive and negative test leads of a TH2523A AC internal resistance tester were then placed in contact with the positive and negative terminals of the battery, respectively. The internal resistance of the battery was read using the internal resistance tester and recorded as the initial battery internal resistance (mΩ) and the battery internal resistance (mΩ) after 800 cycles, respectively.

[0168] 3. Analysis of test results of various embodiments and comparative examples

[0169] Secondary batteries of various embodiments and comparative examples were prepared according to the above methods, and various parameters were measured. The results are shown in Table 1 below.

[0170] Table 1

[0171] According to the results in Table 1, the negative electrode active material of the batteries of Examples 1-12 is a silicon-carbon composite material with a three-dimensional network cross-linked pore structure, and the electrolyte contains a cyclic carbonate compound. Compared with the battery in Comparative Example 1 in which the negative electrode active material is a silicon-carbon composite material with a three-dimensional network cross-linked pore structure and the electrolyte does not contain a cyclic carbonate compound, and the batteries in Comparative Examples 2-3 in which the negative electrode active material is a silicon-carbon composite material with a honeycomb pore structure and the electrolyte contains a cyclic carbonate compound, the batteries of Examples 1-12 exhibit better cycle capacity retention, lower DC impedance and lower gas production.

[0172] In the comparative example, the negative electrode is a silicon-carbon composite material with a honeycomb pore structure. Silicon particles do not easily settle within the honeycomb pore structure. As a result, the mass content of silicon-based particles in the honeycomb pore structure is low, only 7%, and the battery energy density is low. Furthermore, the silicon element is concentrated on the surface of the composite material, making it difficult for the carbon matrix to limit the expansion of the silicon-based particles, resulting in poor battery cycling performance.

[0173] From the comparison between Examples 5-6 and 7-8, it can be seen that controlling the ratio EL:Vm between the pore volume Vm of the silicon-carbon composite material and the mass proportion EL of the cyclic carbonate compound in the electrolyte in the range of 0.05 to 3.5 can further improve the cycle capacity retention rate of the battery and reduce the DC impedance and gas production.

[0174] It can be seen from Examples 9-12 that the cycle performance of the secondary battery is further improved by further controlling the ratio EL:SSA between the mass proportion of the cyclic carbonate compound in the electrolyte and the specific surface area SSA of the silicon-carbon composite material to be 0.00015-0.05 or the ratio EL:V1 between the mass proportion EL of the cyclic carbonate compound in the electrolyte and the total pore volume V1 of pores with a pore diameter of less than or equal to 100 nm in the silicon-carbon composite material to be 1-30.

[0175] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A secondary battery, characterized in that: include A negative electrode plate, the negative electrode plate comprising a silicon-carbon composite material having a three-dimensional network cross-linked pore structure; and An electrolyte, wherein the electrolyte comprises a cyclic carbonate compound, wherein the cyclic carbonate compound is represented by formula I, Wherein, R1 and R2 each independently include at least one of H and C1-C6 alkyl.

2. The secondary battery according to claim 1, characterized in that: The pore volume per unit mass of the silicon-carbon composite material is Vm, in cm 3 / g; In the electrolyte, based on the total mass of the electrolyte, the mass ratio of the cyclic carbonate compound is EL, in units of g / g. EL: Vm is 0.02~5, and can be selected as 0.05~3.

5.

3. The secondary battery according to claim 2, characterized in that: The pore volume per unit mass of the silicon-carbon composite material is Vm in the range of 0.01 to 0.3 cm 3 / g, optional range is 0.02~0.15cm 3 / g.

4. The secondary battery according to any one of claims 1 to 3, characterized in that: In the electrolyte, based on the total mass of the electrolyte, the mass ratio of the cyclic carbonate compound is EL, in units of g / g. The specific surface area of ​​the silicon-carbon composite material is SSA, EL: SSA is 0.00001~0.15, and can be selected as 0.00015~0.

05.

5. The secondary battery according to any one of claims 1 to 4, characterized in that: The specific surface area SSA of the silicon-carbon composite material is 2 to 10 m 2 / g; 3~7m can be selected 2 / g.

6. The secondary battery according to any one of claims 1 to 5, characterized in that: The total pore volume of the pores with a pore diameter of less than or equal to 100 nm in the silicon-carbon composite material is V1cm 3 / g, in the electrolyte, based on the total mass of the electrolyte, the mass proportion of the cyclic carbonate compound is EL, and the unit is g / g, EL: V1 is 0.05~50, and can be selected as 1~30.

7. The secondary battery according to any one of claims 1 to 6, characterized in that: The silicon-carbon composite material has a V1 of ≥ 0.001 cm 3 / g, optional range is 0.005~0.01cm 3 / g.

8. The secondary battery according to any one of claims 1 to 7, characterized in that: The cyclic carbonate compound is at least one selected from ethylene carbonate, propylene carbonate, 1,2-butanediol carbonate, and 4,5-dimethylethylene carbonate.

9. The secondary battery according to any one of claims 1 to 8, characterized in that: The silicon-carbon composite material comprises: a carbon matrix having a three-dimensional network cross-linked pore structure; and silicon nanoparticles at least partially embedded in the three-dimensional network cross-linked pore structure of the carbon matrix.

10. The secondary battery according to claim 9, characterized in that: The mass ratio of the silicon nanoparticles in the silicon-carbon composite material is greater than or equal to 40%, and can be optionally 40-60%.

11. The secondary battery according to claim 9 or 10, characterized in that: The silicon nanoparticles include one or more of silicon-oxygen compounds, amorphous silicon, crystalline silicon and silicon-carbon composites.

12. The secondary battery according to any one of claims 9 to 11, characterized in that: The carbon matrix includes one or more of graphite, soft carbon and hard carbon.

13. The secondary battery according to any one of claims 9 to 12, characterized in that: The total volume of the pores with a pore size greater than 100 nm in the carbon matrix particles is recorded as Vc1cm 3 / g, the total volume of the pores with a pore size of less than or equal to 100 nm in the carbon matrix particles is recorded as Vc2cm 3 / g, the carbon matrix particles satisfy: 1<Vc2 / Vc1≤30; optionally, 3≤Vc2 / Vc1≤25.

14. The secondary battery according to any one of claims 1 to 13, characterized in that: The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20000N is P11g / cm 3 The compaction density of the silicon-carbon composite material after 20 times of powder compaction under a force of 20000N is P21g / cm 3 The ratio satisfies: 1.00<P21 / P11≤1.20, optionally, 1.02≤P21 / P11≤1.

10.

15. The secondary battery according to any one of claims 1 to 14, characterized in that: The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20000N is P11g / cm 3 Satisfies: 1.10≤P11≤1.40, optionally, 1.12≤P11≤1.

35.

16. The secondary battery according to any one of claims 1 to 15, characterized in that: The secondary battery includes at least one of a lithium ion battery, a sodium ion battery, a magnesium ion battery, and a potassium ion battery.

17. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 16.